Exoneration Clause in Freight Forwarding Agreements from the Perspective of Consumer Protection - Indah Nuraini; Nur Handayati; Wahyu Prawesti; Hartoyo Hartoyo; Noenik Soekorini (Journal of International Multidisciplinary Research, 2025)
Freight forwarding agreements in Indonesia frequently contain exoneration clauses that exempt logistics providers from liability for loss or damage, raising serious concerns regarding consumer protection. While such clauses are designed to manage contractual risk, they often conflict with the principles enshrined in Law No. 8 of 1999 on Consumer Protection (UUPK), particularly those ensuring fairness, good faith, and legal accountability. This study investigates the legality and ethical implications of exoneration clauses within standard-form freight forwarding contracts used by companies such as JNE, TIKI, and SiCepat. Employing a doctrinal legal research methodology, the study integrates statutory, conceptual, and case-based approaches to analyze primary legislation, judicial decisions, and relevant legal doctrines. It critically evaluates the use of these clauses in light of consumer rights, contract theory, and the economic impact on service quality. Findings reveal that exoneration clauses not only contravene the UUPK but also create systemic contractual imbalances due to the lack of negotiation opportunities and transparency. The study proposes a normative legal framework for reform, including clause classification, interactive consent mechanisms, and regulatory enforcement to ensure contractual fairness. This research contributes to both legal scholarship and policy development by highlighting the urgent need for doctrinal clarity and regulatory oversight in Indonesia's logistics sector.